Nonsense variant of NR0B1 causes hormone disorders associated with congenital adrenal hyperplasia - Da-Bei Fan (Nature Portfolio, 2021)
Abstract Congenital adrenal hyperplasia (CAH) is a rare X-linked recessive inherited disease that is considered a major cause of steroidogenesis disorder and is associated with variants or complete deletion of the NR0B1 gene. The DAX-1 protein (encoded by NR0B1) is a vertebrate-specific orphan nuclear receptor and is also a transcriptional factor for adrenal and reproductive development. CAH usually causes adrenal insufficiency in infancy and early childhood, leading to hypogonadotropic hypogonadism in adulthood; however, few adult cases have been reported to date. In this study, we examined a Chinese family with one adult patient with CAH, and identified a putative variant of NR0B1 gene via next-generation sequencing (NGS), which was confirmed with Sanger sequencing. A novel nonsense variant (c.265C>T) was identified in the NR0B1 gene, which caused the premature termination of DAX-1 at residue 89 (p.G89*). Furthermore, mutant NR0B1 gene displayed a partial DAX-1 function, which may explain the late pathogenesis in our case. Additionally, qPCR revealed the abnormal expression of four important genes identified from ChIP-seq, which were associated with energy homeostasis and steroidogenesis, and were influenced by the DAX-1 mutant. In addition, hormone disorders can be caused by DAX-1 mutant and partially recovered by siRNA of PPARGC1A. Herein, we identified a novel nonsense variant (c.265C>T) of NR0B1 in a 24-year-old Chinese male who was suffering from CAH. This mutant DAX-1 protein was found to have disordered energy homeostasis and steroidogenesis based on in vitro studies, which was clinically consistent with the patient’s phenotypic features.